IMPROVING LEARNING OUTCOMES IN PHYSICS SCIENCE THROUGH INQUIRY GUIDED LEARNING STUDENTS IN CLASS IX 5 SMP NEGERI 17 PEKANBARU - T. Etty Betriza (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2017)
This research aimed to improve student learning outcomes through the implementation of guided inquiry learning model on electrical dynamic materials in class IX 5 SMP Negeri 17 Pekanbaru. Based on the problems of class IX 5 students in physics science learning: students consider that physics is difficult and the learning outcomes of some students are still below the minimum mastery criteria, it is necessary to apply inquiry learning model, that is one model that can improve student learning outcomes. This research is a classroom action research with three cycles on dynamic electrical materials. The subjects of the research were the students of class IX 5 SMPN 10 which amounted to 42 student. The research instrument is a test of learning outcomes (postest) and observation sheet. The data collection technique uses the learning outcomes test technique, which is given after one cycle is implemented in accordance with the material discussed. Student learning outcomes are collected and analyzed descriptively to provide an overview of the improvement of student learning outcomes. The result of the research is the improvement of learning outcomes from cycle I to cycle III that is in the first cycle of students who complete 69.05% with the average value of 80.6, in the second cycle of students who complete 85.71% with the average value of 82.5 and in the third cycle of students who complete 95.24% with the average value 83.3. Thus the implementation of guided inquiry learning can improve learning outcomes physics students class IX 5 SMP 17 Pekanbaru on dynamic electrical materials.